(untitled) (Journal of Applied Oral Science, 2022)
Objectives: To analyze the association between periodontal conditions and inflammation, nutritional status and calcium-phosphate metabolism disorders in hemodialysis (HD) patients. Material and Methods: We analyzed 128 HD patients divided into two groups: dentate (n = 103) and edentulous (n=25). The following items were assessed: baseline characteristics, age at the start and duration of HD, biochemical data: C-reactive protein (CRP), serum albumin, calcium, phosphorus, alkaline phosphatase, parathormone. A single dentist performed a complete dental/periodontal examination, including parameters of oral hygiene and gingival bleeding. Results: One person had healthy periodontium, 62.14% of the patients had gingivitis, and 36.9% had moderate or severe periodontitis. The age at HD onset had a positive impact on periodontal status and negatively correlated with the number of teeth. A positive correlation between age and CRP level and negative correlations between age and serum albumin and phosphorus were found. Pocket depth (PD) was negatively correlated with serum albumin. The number of teeth was negatively correlated with serum CRP. Conclusions: High prevalence and severity of periodontal disease are observed in hemodialysis patients. There is a high probability that periodontal disease may be present at the early stages of chronic kidney disease (CKD) before the hemodialysis onset.